2014
DOI: 10.1074/mcp.m114.038075
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation of the N-terminal Region of the Serine-rich Adhesin Srr1 of Streptococcus agalactiae Explored by Mass Spectrometry

Abstract: Serine-rich (Srr) proteins exposed at the surface of Gram-positive bacteria are a family of adhesins that contribute to the virulence of pathogenic staphylococci and streptococci. Lectin-binding experiments have previously shown that Srr proteins are heavily glycosylated. We report here the first mass-spectrometry analysis of the glycosylation of Streptococcus agalactiae Srr1. After Srr1 enrichment and trypsin digestion, potential glycopeptides were identified in collision induced dissociation spectra using X!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 82 publications
1
29
0
Order By: Relevance
“…Structural studies of GtfC identified a conserved loop region that is crucial for acceptor substrate binding from GtfC homologs in streptococci (Zhu et al, 2015a). Mass spectrometry analysis of purified Srr1 unambiguously demonstrates that Serine or Threonine resides on Srr1 was modified by GlcNAc and Glc, which resembles the findings of Srr2 (Chaze et al, 2014). Interestingly there is a novel modification found on Srr1, which was identified as O -acetylated- N -acetylhex-osamine (Chaze et al, 2014).…”
Section: Surface Protein Glycosylation In Bacteria Found In the Gut Mmentioning
confidence: 53%
See 1 more Smart Citation
“…Structural studies of GtfC identified a conserved loop region that is crucial for acceptor substrate binding from GtfC homologs in streptococci (Zhu et al, 2015a). Mass spectrometry analysis of purified Srr1 unambiguously demonstrates that Serine or Threonine resides on Srr1 was modified by GlcNAc and Glc, which resembles the findings of Srr2 (Chaze et al, 2014). Interestingly there is a novel modification found on Srr1, which was identified as O -acetylated- N -acetylhex-osamine (Chaze et al, 2014).…”
Section: Surface Protein Glycosylation In Bacteria Found In the Gut Mmentioning
confidence: 53%
“…Mass spectrometry analysis of purified Srr1 unambiguously demonstrates that Serine or Threonine resides on Srr1 was modified by GlcNAc and Glc, which resembles the findings of Srr2 (Chaze et al, 2014). Interestingly there is a novel modification found on Srr1, which was identified as O -acetylated- N -acetylhex-osamine (Chaze et al, 2014). However, it still remains unknown what enzyme is responsible for the modification.…”
Section: Surface Protein Glycosylation In Bacteria Found In the Gut Mmentioning
confidence: 53%
“…E). This finding provides further indication that the SSR variants are glycosylated: the glycan content of SRR proteins is known to alter their electrophoretic mobility, leading to a slower migration pattern and to detection of protein bands with a higher apparent molecular mass (Takamatsu et al ., ; Mistou et al ., ; Yen et al ., ; Chaze et al ., ). As SrpA was expressed at a higher level than SrpB and SrpC, the band representing SrpA 1000flag was excised and digested with trypsin, and the resulting peptides extracted and subjected to liquid chromatography coupled to mass spectrometry analysis (LC‐MS/MS).…”
Section: Resultsmentioning
confidence: 97%
“…For the 8 peptides located in the SRR2 domain, the maximum number of HexNAc and O‐ AcHexNAc residues anchored to a peptide sequence was close to the number of serine/threonine residues in the sequence. This observation suggests that these peptides contain either HexNAc or O ‐AcHexNAc modifications, as shown for Srr1 of S. agalactiae (Chaze et al ., ), and that all serine and threonine residues located in the C‐terminal SRR2 domain are glycosylated. Glycosylation with a Hex residue was found only on peptides carrying at least 3 HexNAc residues, suggesting that HexNAc modification is a prerequisite for Hex glycosylation.…”
Section: Resultsmentioning
confidence: 99%
“…The glycan sequence of the Fap1 peptide backbone has been determined as Rha1-3Glc1-(Glc1-3Glc NAc1-) 2, 6Glc1-6GlcNAc . The glycosyl composition of other SRRPs has been determined for GspB of Streptococcus gordonii (Takamatsu et al 2004) and Srr1 of Streptococcus agalactiae (Chaze et al 2014), but the sequential order of the glycans are unknown.…”
Section: Glycosyltransferases Important For the Glycosylation Of Srrpsmentioning
confidence: 99%